2014
DOI: 10.1017/s0305000914000543
|View full text |Cite
|
Sign up to set email alerts
|

Developing communicative competence: a longitudinal study of the acquisition of mental state terms and indirect requests

Abstract: This longitudinal study involving 101 Dutch four- and five-year-olds charts indirect request (IR) and mental state term (MST) understanding and investigates the role that Theory of Mind (ToM) and general linguistic ability (vocabulary, syntax, and spatial language) play in this development. The results showed basic understanding of IR and MST in four-year-olds, but full understanding had not been reached even at five years old. Furthermore, although ToM predicted both IR and MST when linguistic ability was not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…Findings indicating that associations diminished when controlling for mental age and MLU likely reflect the strong relationship between theory of mind and highlight the role of syntactic development in particular (de Villiers, 2007). For instance, De Mulder (2015) found that syntactic ability predicted the understanding of indirect requests (e.g. shivering to signal to another person that they should turn up the heat) in TD children.…”
Section: Discussionmentioning
confidence: 99%
“…Findings indicating that associations diminished when controlling for mental age and MLU likely reflect the strong relationship between theory of mind and highlight the role of syntactic development in particular (de Villiers, 2007). For instance, De Mulder (2015) found that syntactic ability predicted the understanding of indirect requests (e.g. shivering to signal to another person that they should turn up the heat) in TD children.…”
Section: Discussionmentioning
confidence: 99%
“…For example, use and understanding of mental state terms, which refer to one's emotional or cognitive state, require theory of mind. 33 Similarly, correct use of personal pronouns requires the speaker to know if the communication partner is aware of the referent. If not, a communication breakdown can occur.…”
Section: Language Overview In Autism Spectrum Disordermentioning
confidence: 99%
“…Moore et al (1990), for example, looked at four-year-olds' understanding of both mental state verbs ('know' and 'think') and modal auxiliaries ('must' and 'might') and demonstrated that the children's understanding of the mental terms was related to their understanding of beliefs. Similarly, De Mulder (2015) found an association between the understanding of mental state verbs, modal auxiliaries and modal adjuncts and ToM development in typically developing Dutch-speaking four-and five-year-olds. Furthermore, Papafragou (2001), Papafragou and Li (2001) and Ifantidou (2005) have all argued that children's acquisition of evidential markers (the linguistic encoding of information source), is constrained by the development of ToM, in particular the understanding of the source of beliefs and speaker certainty.…”
Section: Theory Of Mind and The Acquisition Of Epistemic Modal Auxilimentioning
confidence: 68%
“…This study investigated the relationship between ToM and the understanding of epistemic modal auxiliaries in Dutch typically developing and autistic children. Given the finding from previous research that Dutch five-year-olds demonstrate a basic understanding of the Dutch epistemic modal auxiliary system (De Mulder, 2015), it was expected that the typically developing six-year-olds would be capable of understanding the strength distinctions between the various epistemic modal auxiliaries. This expectation was indeed borne out by the data: the typically developing six-year-olds showed above chance performance in their understanding of the epistemic terms.…”
Section: Discussionmentioning
confidence: 99%